Redesain Lembaga Kepresidenan - Anang Fajri Perdana; Annisa Fidantas Shafir (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
The Presidential Institution is a constitutional body that plays a central role in Indonesia's presidential system of government as regulated by the 1945 Constitution of the Republic of Indonesia (UUD NRI 1945). However, to this day, there is no specific law that systematically and comprehensively regulates the status, structure, authority, and accountability mechanisms of the Presidential Institution. This regulatory vacuum has given rise to several legal and administrative problems in the practice of state governance, including the absence of limitations on the number of ministries (Article 17 of the 1945 Constitution), the proliferation of deputy ministerial positions that lack explicit legal basis under Law No. 39 of 2008 on State Ministries, overlapping roles between coordinating ministers and technical ministers, and the lack of a clear legal foundation for the appointment of presidential special staff, including millennial special staff. This paper employs a normative juridical approach to examine the urgency of enacting a Law on the Presidential Institution in order to strengthen legal certainty, bureaucratic efficiency, as well as the principles of transparency and accountability in government administration. The study concludes that without an adequate legal framework, the exercise of executive power tends to become excessive and prone to abuse. Therefore, the establishment of a Law on the Presidential Institution is an urgent necessity for the consolidation of democracy and the supremacy of the Constitution.